Across type, time and space American grand strategy in comparative perspective - Dombrowski, Peter J. 1963-; Reich, Simon 1959- (Cambridge elements, 2021)
The field of grand strategy is exceptionally American-centric theoretically, methodologically and empirically. Indeed, many scholars treat the United States as a unique case, and thus incomparable. This Element addresses the shortcomings of this approach by developing a novel framework for the purpose of systematic comparison, both within and among different countries. Using the United States as a benchmark, three dimensions are considered in which grand strategy can be compared: first, attributes of the major types commonly discussed in the literature; second, similarities and differences in the implementation of grand strategies over time, using US strategic relations with contemporary Russia as an example; and finally, across space, properties of the grand strategies that are interactively employed by other major powers in relation to the United States in the Indo-Pacific. The Element can be used by scholars and students alike to expand analysis beyond the confines that currently dominate the field